Enhanced network reconstruction from irreducible local information - Rossana Mastrandrea; Tiziano Squartini; Giorgio Fagiolo; Diego Garlaschelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
Network topology plays a key role in many phenomena, from the spreading of diseases to that of financial crises. Whenever the whole structure of a network is unknown, one must resort to reconstruction methods that identify the least biased ensemble of networks consistent with the partial information available. A challenging case is when there is only local (node-specic) information available. For binary networks, the relevant ensemble is one where the degree (number of links) of each node is constrained to its observed value. However, for weighted networks the problem is much more complicated. While the naive approach prescribes to constrain the strengths (total link weights) of all nodes, recent counter-intuitive results suggest that in weighted networks the degrees are often more informative than the strengths, and as 'fundamental' as the latter. This implies that the reconstruction of weighted networks would be signicantly enhanced by the specication of both quantities, a computationally hard and bias-prone procedure. Here we solve this problem by introducing an analytical and unbiased maximum-entropy method that works in the shortest possible time and does not require the explicit generation of reconstructed samples. We consider several real-world applications and show that, while the strengths alone give poor results, the additional knowledge of the degrees yields accurately reconstructed networks. Information-theoretic criteria rigorously conrm that the binary information is irreducible to the weighted one. Our results have strong implications for the analysis of motifs and communities and whenever the reconstructed ensemble is required as a null model to detect higher-order patterns.
Keywords: 330; Network reconstruction; Null models; Complex networks; Maximum entropy ensembles; Configuration model